Protein-Truncating Variants at the Cholesteryl Ester Transfer Protein Gene and Risk for Coronary Heart Disease - Nomura, Akihiro; Won, Hong-Hee; Khera, Amit V.; Takeuchi, Fumihiko; Ito, Kaoru; McCarthy, Shane; Emdin, Connor A.; Klarin, Derek; Natarajan, Pradeep; Zekavat, Seyedeh M.; Gupta, Namrata; Peloso, Gina M.; et al. (Circulation research, 2017)
Therapies that inhibit CETP (cholesteryl ester transfer protein) have failed to demonstrate a reduction in risk for coronary heart disease (CHD). Human DNA sequence variants that truncate the gene may provide insight into the efficacy of CETP inhibition. To test whether protein-truncating variants (PTVs) at the gene were associated with plasma lipid levels and CHD. We sequenced the exons of the gene in 58 469 participants from 12 case-control studies (18 817 CHD cases, 39 652 CHD-free controls). We defined PTV as those that lead to a premature stop, disrupt canonical splice sites, or lead to insertions/deletions that shift frame. We also genotyped 1 Japanese-specific PTV in 27561 participants from 3 case-control studies (14 286 CHD cases, 13 275 CHD-free controls). We tested association of PTV carrier status with both plasma lipids and CHD. Among 58 469 participants with gene-sequencing data available, average age was 51.5 years and 43% were women; 1 in 975 participants carried a PTV at the gene. Compared with noncarriers, carriers of PTV at had higher high-density lipoprotein cholesterol (effect size, 22.6 mg/dL; 95% confidence interval, 18-27; <1.0×10 ), lower low-density lipoprotein cholesterol (-12.2 mg/dL; 95% confidence interval, -23 to -0.98; =0.033), and lower triglycerides (-6.3%; 95% confidence interval, -12 to -0.22; =0.043). PTV carrier status was associated with reduced risk for CHD (summary odds ratio, 0.70; 95% confidence interval, 0.54-0.90; =5.1×10 ). Compared with noncarriers, carriers of PTV at displayed higher high-density lipoprotein cholesterol, lower low-density lipoprotein cholesterol, lower triglycerides, and lower risk for CHD.